Molecular characterization of Hoya mindorensis Schlechter by Microsatellite Markers (The Philippine Journal of Crop Science, 2014)
Hoya mindorensis Schlechter is an ornamental plant endemic to the Philippines. The aim of this study was to identify microsatellite primers that could discriminate different accessions of H Mindorensis and to determine the genetic diversity in those accessions. Sixteen accessions collected from different areas in the Philippines were used as plant materials. Since no microsatellite primer has been established for the Hoya genus, 12 primer pairs in Amsonia kearneyana (Apocynaceae) were utilized. Among them, four compatible SSR markers were successfully transferred. An average of 6.5 bands per primer set was obtained, 4.75 of it was polymorphic. The total polymorphic bands obtained were as high as 73.1%. The molecular characterization suggested that these accessions can be grouped by Jaccard similarity test into four clusters. Further studies utilizing the four compatible primers to analyze genetic diversity within other species of Hoya or among species of Hoya genus was suggested to check whether the primers would also be transferable to other Hoya species or only specific to H. mindorensis.